2009
DOI: 10.3177/jnsv.55.1
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Antioxidant Vitamins in Maternal and Cord Serum and Their Effect on Birth Outcomes

Abstract: Summary Background: Emerging evidence indicates that maternal oxidative stress during pregnancy could impair fetal growth and that antioxidant vitamins (e.g. vitamins A, E and C) have a significant role in miantaining physiological processes of pregnancy and growth. Aims: To determine the concentrations of vitamins A, E, and C in pair-matched maternal and cord serum samples of neonate, and thus to investigate the relationship between maternal serum levels of these vitamins at delivery and birth outcomes. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 44 publications
9
27
2
1
Order By: Relevance
“…The baseline serum alpha tocopherol levels of the study control and supplemented groups were similar to the levels reported by other studied similar populations [4,26,27]. However, the study results are higher than those reported by Rodriguez et al [28], but the difference may stem from the population studied by the latter, namely, a population living in poverty with terrible health indicators.…”
Section: Discussioncontrasting
confidence: 56%
“…The baseline serum alpha tocopherol levels of the study control and supplemented groups were similar to the levels reported by other studied similar populations [4,26,27]. However, the study results are higher than those reported by Rodriguez et al [28], but the difference may stem from the population studied by the latter, namely, a population living in poverty with terrible health indicators.…”
Section: Discussioncontrasting
confidence: 56%
“…The role of anti-oxidant vitamins (C and E) in the maintaining of physiological process of fetal growth during pregnancy was reported by Wang et al (2009). Brion et al (2003) confirmed that preterm infants have lower antioxidant vitamins in their serum compared with term controls.…”
Section: Discussionmentioning
confidence: 75%
“…This result corroborates with previous studies that found similar findings, they explained their results by that placenta is permeable to dehydroascorbic acid but not to ascorbic acid then the fetus converts dehydroascorbic acid to ascorbic acid and accumulates it. 15,16 Also increased vitamin C levels in cord blood could be due to fetal synthesis of vitamin as dehydroascorbic acid, the oxidized form of ascorbic acid, that is reduced to L-ascorbic acid by fetal erythrocytes that gets trapped in the fetal circulation. 17 In our study a positive significant correlation between vitamin C levels of mothers and cord blood vitamin C levels was detected.…”
Section: Discussionmentioning
confidence: 98%